2015
DOI: 10.1371/journal.pone.0139937
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Work-Related Functional Impairment prior to Suicide

Abstract: BackgroundWork-related functional impairment in terms of sickness absence and disability pension (SA/DP) has been reported to be associated with subsequent suicide. However, there is only limited knowledge on SA/DP patterns prior to suicide. The aim was to identify trajectories of work-related functional impairment prior to suicide and to describe associations of socio-demographic and medical factors with such trajectories.MethodsThis is a population-based retrospective cohort study of the 4 209 individuals ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
1
10
2
Order By: Relevance
“…These findings are comparable to results from a recently published study, which showed five different trajectories of SA/DP before suicide [ 10 ]. However, a larger proportion of individuals (30%) in that previous study had stable high levels of SA/DP months over time before suicide, which was twice as much as among suicide attempters in the current study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are comparable to results from a recently published study, which showed five different trajectories of SA/DP before suicide [ 10 ]. However, a larger proportion of individuals (30%) in that previous study had stable high levels of SA/DP months over time before suicide, which was twice as much as among suicide attempters in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…However, a larger proportion of individuals (30%) in that previous study had stable high levels of SA/DP months over time before suicide, which was twice as much as among suicide attempters in the current study. Also, this group of individuals had around 11 months of SA/DP during 4 years before suicide [ 10 ], which was moderately higher than the corresponding group in our findings. On the other hand, there was a larger proportion of young suicide attempters with constantly no or low level of SA/DP months (62%) in our study compared to the low SA/DP trajectory (46%) before suicide [ 10 ].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…We used the likelihood ratio tests to evaluate whether the characteristics were associated with all five trajectory groups in the full model including all covariates. Moreover, Nagelkerke pseudo-R 2 were estimated to measure the strength of these associations 18. Each factor was consecutively excluded and reincluded from the full model in order to calculate the differences in R 2 and to test the contribution of a given factor to the full model.…”
Section: Methodsmentioning
confidence: 99%
“…These approaches have mostly been used to capture unknown heterogeneity in work-related factors and to see their association with some health outcomes. For example, to study the association between occupational complexity and cognition in later life (13), work characteristics and hypertension (14), absenteeism trajectories and health factors (15), or work functioning and return to work after sick leave (16), among other similar studies (17,18,19,20). In summary, these approaches allow us to address labor market changes from a life course perspective (21).…”
mentioning
confidence: 99%